UKRAINIAN TIME: GRAMMATICAL INTERPRETATION - Barchuk, V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
In the article the system and hierarchy structure of temporal meaning in Ukrainian language is established. It is suggested that interval, tense and taxis represent the ontological time. The category of interval is the main and the most branched out in Ukrainian grammar system of verb. Tense are dominant as bases temporal component of the human consciousness. Ukrainian language has thirty variants of grammatical time meaning.